Calculation of Semi-major and Semi-minor Radii and Deformation Parameters for Molybdenum 86-10042Mo Isotopes - Mohammed, Reem gani abdulrazzaq; Ebrahiem, Sameera Ahmed; Shareef, Mustafa H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study explores the nuclear properties of even-numbered molybdenum () isotopes in the mass range 86 to 100. It focuses on the calculations of fundamental nuclear properties such as distortion coefficients ( and ), electric quadrupole moments (Q₀), root-mean-square charge radii, and reduced transition probabilities B(E2)↑. These calculations were derived using a theoretical framework based on the distorted shell model and implemented in MATLAB. The evaluation also included the identification of the two quasi-nuclear shape axes (major and minor), from which three-dimensional representations of the isotopic shapes were generated.The analysis revealed a gradual decrease in distortion coefficients and transition probabilities with increasing mass number, indicating a trend toward nuclear stability. We observed a significant decrease in distortion near the magic number of neutrons, demonstrating the enhanced stability resulting from closed shells. The results are in good agreement with theoretical predictions and experimental data, providing a deeper understanding of the behavior of molybdenum isotopes and contributing to the expansion of knowledge of nuclear shape evolution, charge distribution, and nuclear transitions in intermediate-mass nuclei.